Banking and finance on the Internet - Cronin, Mary J. (New York : John Wiley & Sons, 1998)
Every business day, banks, brokerage houses, and other institutions transfer millions of dollars around the globe at the speed of light. Yet the financial services industry has just begun to harness the power of the worldwide network known as the Internet. The book offers bankers, mutual fund managers, and other financial services decision makers insight on crafting effective online commerce strategies of their own.
Includes bibliographical references (p. 304-305) and index.
oif 21/05/13
Loan
Keywords: Banks and banking - computer network resources; Investments - computer network resources; World Wide Web (Information retrieval system).; Investments- data processing; Banks and banking - data processing; Internet (Computer network).